Ключові проблеми безпеки у технологіях бездротового зв'язку 5G - Чибізов, І. О. (ХНУРЕ, 2024)
5G is the fifth generation of mobile communications that offers significantly higher speed, bandwidth and reliability compared to 4G. The growing use of 5G in various industries, such as the Internet of Things (IoT), autonomous vehicles, and telemedicine, makes the issue of 5G communication security extremely important. Previous generations of mobile networks had the primary goal of providing fast and reliable data services to users. However, 5G extends this concept by offering a wide range of wireless services through different access platforms and multi-layer networks. It is through services that the main issues of technology security will be considered in this work.
Keywords: бездротовий зв'язок 5G; архітектура 5G